The Effect of Photopriode Differences to The Growth of Population Microalga Haematococcus pluvialis - Sri Midawati Agustina Panjaitan; Saberina Hasibuan; Syafriadiman Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis research was conducted in April-Juni 2019 at the Natural Feed Laboratory, BBAT Sungai Gelam. Jambi. The purpose of this study was to determine the best photoperiod in increasing the growth rate and biomass production of microalga H. pluvialis . The method used in this research was experimental using Completely Random Design (CRD) one factor with four treatments and repeated three times. The treatments used was P1 24 bright (24B), P2 20 bright 04 dark (20B : 04D), P3 16 bright 08 dark (16B : 08D), P4 12 bright 12 dark (12B : 12D). Cultivation was carried out for ten days, using Walne. The results showed that the treatment of the dark cycle and the light cycle affected the population density and specific growth rate. Lighting 16 hours Bright  08 hours Dark gave the best results with a cell density of 888 x 104 cells / ml and a specific growth rate of 0,353 cells/ml/day with peak growth occurring on the day eight. Water quality parameters during the study were optimal for the growth of microalga H. pluvialis with a water temperature of 21,05-23,78 0C, pH 7,70-8,78 and dissolved oxygen 5,54-6,30 mg /L. Keywords: Photopriode, Growth of Population, Haematococcus pluvialis.